Temporal changes in benthic macroinvertebrates and their interactions with fish predators after restoration in the Cheonggyecheon, a downtown stream in Seoul, Korea. Issue 6 (13th November 2014) - Choe, Lak Jung; Jung, Sang Woo; Kim, Dong Gun; Baek, Min Jeong; Kang, Hyo Jeong; Lee, Cha Young; Bae, Yeon Jae
Abstract The Cheonggyecheon (Cheonggye stream), a downtown stream in Seoul, Korea, was restored by the historic Cheonggyecheon Restoration Project (2003–2005), and its discharge and other environmental conditions are artificially regulated throughout the year. The aim of this study was to assess temporal changes in benthic macroinvertebrates and their interactions with fish predators in the Cheonggyecheon. Sampling was conducted twice a year (spring and autumn) at three sections of the stream from 2006 to 2010 using a Surber sampler (50 × 50 cm) for benthic macroinvertebrates and a cast net (mesh size, 10 × 10 mm) and a kick net (mesh size, 5 × 5 mm) for fishes. Analyses of annual precipitation and most water quality parameters showed no significant differences across the study period (P > 0.05). The species richness and density of benthic macroinvertebrates and fishes varied across the sampling period. Analyses of functional feeding groups and trophic guilds showed distinct trends, such as an increase in the number of insectivorous fish in the absence of invertebrate predators. Correlation and regression analyses for five major groups of benthic macroinvertebrates and fishes demonstrated that the density of certain groups of benthic macroinvertebrates (e.g. Tubificidae, Erpobdellidae, Baetidae, and Chironomidae) and insectivorous fishes (e.g. Gobioninae, Leuciscinae, Danioninae, and Gobiidae) were negatively correlated. In conclusion, in an artificially regulated stream like the restored Cheonggyecheon, where physical environments are nearly unchanged, fish predation can be a major factor controlling benthic macroinvertebrate communities.